Bioprocessing of Recombinant CHO‐K1, CHO‐DG44, and CHO‐S: CHO Expression Hosts Favor Either mAb Production or Biomass Synthesis. Issue 3 (11th June 2018) - Reinhart, David; Damjanovic, Lukas; Kaisermayer, Christian; Sommeregger, Wolfgang; Gili, Andreas; Gasselhuber, Bernhard; Castan, Andreas; Mayrhofer, Patrick; Grünwald‐Gruber, Clemens; Kunert, Renate
Abstract : Chinese hamster ovary (CHO) cells comprise a variety of lineages including CHO‐DXB11, CHO‐K1, CHO‐DG44, and CHO‐S. Despite all CHO cell lines sharing a common ancestor, extensive mutagenesis, and clonal selection has resulted in substantial genetic heterogeneity among them. Data from sequencing show that different genes are missing in individual CHO cell lines and each cell line harbors a unique set of mutations with relevance to the bioprocess. However, not much literature is available about the influence of genetic differences of CHO on the performance of bioprocess operations. In this study, the host cell‐specific differences among three widely used CHO cell lines (CHO‐K1, CHO‐S, and CHO‐DG44) and recombinantly expressed the same monoclonal antibody (mAb) in an isogenic format by using bacterial artificial chromosomes (BACs) as transfer vector in all cell lines is examined. Cell‐specific growth and product formation are studied in batch, fed‐batch, and semi‐continuous perfusion cultures. Further, two different cell culture media are used to investigate their effects. The authors find CHO cell line‐specific preferences for mAb production or biomass synthesis that are determined by the host cell line. Additionally, quality attributes of the expressed mAb are influenced by the host cell line and media. Abstract : Chinese hamster ovary (CHO) cells comprise a variety of lineages. Despite all CHO cell lines sharing a common ancestor, extensive mutagenesis, and clonal selection has resulted in substantial genetic heterogeneity among them. Data from sequencing show that different genes are missing in individual CHO cell lines and each cell line harbors a unique set of mutations with relevance to the bioprocess. The host cell‐specific differences among three widely used CHO cell lines and recombinantly expressed the same monoclonal antibody (mAb) in an isogenic format by using bacterial artificial chromosomes (BACs) as transfer vector in all cell lines is examined.